Charitable Clicks and Financial Frontiers: Analyzing the Interplay of Digital Giving and Inclusive Economics - Dewi Samad, Telsy Fratama; Muhaimin Yusof, Ku Abdul (Journal of Contemporary Applied Islamic Philanthropy, 2025)
Purpose: This study explores how digital alms-giving serves as a transformative force in advancing financial inclusion within an increasingly digitized economy. Methodology: Through a systematic literature review, the research synthesizes global evidence showing that digital charitable platforms not only expand access to financial services for underserved populations but also enhance financial literacy, foster community resilience, and contribute to macroeconomic growth. Despite facing challenges such as digital inequality, trust issues, and regulatory gaps, digital alms-giving demonstrates high potential to bridge socio-economic disparities by integrating technology with culturally rooted philanthropic values. Findings: The findings offer strategic insights for policymakers, fintech innovators, and philanthropic institutions seeking inclusive financial solutions in line with sustainable development goals, and ultimately conclude that digital alms-giving can be a scalable and sustainable instrument for achieving equitable economic empowerment.